Work in progress?: 14-16 year old boys' experience of vocational education - Gilchrist, Rosemary Martine (2015)
This research arose from my professional concern, as a teacher, in boys’ underachievement in secondary schools, an issue that has occupied a central position in educational debate in recent years. My study focused on how the 14-19 curriculum changes, introduced by the last Labour Government, might have some enduring relevance to the debate on boys and achievement. The first two research questions considered perspectives on achievement and interventions aiming to benefit boys while the final question related to experiences of the 14-19 curriculum. Review of the literature led me to employ a critical theoretical framework The methodology used was qualitative in nature in which I adopted a post-modern interpretivist perspective. Data was collected through semi-structured interviews with young people and with their teachers in a number of English schools and colleges with some accompanying policy document review. Semiotic analysis was also employed to examine the use and implications of language and how this can alter perspectives of all those involved in education. Analysis of the data related to the key categories underpinning the research questions and using a methodology informed by grounded theory. Key issues arising related to the concepts of ‘choice’, ‘practicality’ and ‘being treated as adults’. In conducting the research I was most interested in finding out whether and how policy intentions can translate into practical outcomes and how the needs and voices of young people can be articulated for their benefit and for that of the wider society. My findings suggest that the issue of underachievement is systemic within the mainstream educational curriculum with a gap existing between what young people think they need and what policy makers perceive to be required. I propose that there is need for renewed attention specific to learners aged 14-16 which will enable the development of skills and enhance life choices so that achievement is better understood, inclusive and accessible